Analisis Kualitas Pelayanan Digital Pospay dan Tantangan Budaya Transaksi Konvensional Masyarakat pada Kantor Pos Cabang Utama Kota Surabaya - Yusinta Fitrianti; Haryo Kunto Wibisono (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The structural realignment of public sector governance, catalyzed by rapid technological evolution, has compelled PT Pos Indonesia to institute the Pospay digital ecosystem. Nonetheless, this paradigm shift frequently collides with deeply entrenched sociological resistance in empirical settings. This inquiry endeavors to scrutinize the service quality of Pospay while exploring the systemic challenges posed by conventional transaction habits at the Main Branch Post Office in Surabaya. Adopting a descriptive qualitative approach, empirical data were garnered through semi-structured interviews, non-participant field observations, and institutional document analysis. Informants were selected via purposive sampling, encapsulating the operational manager, a front-line service officer, and a service consumer. Data processing adhered to the interactive analysis framework of Miles, Huberman, and Saldaña (2014). Framed through Parasuraman’s SERVQUAL model, the analytical results demonstrate that while the responsiveness and assurance parameters operate at an optimal level, the reliability dimension remains disrupted by sporadic system latency. More significantly, a profound cultural lag actively decelerates this technological migration. Service users manifest a chronic reliance on physical counters, structured by marginal digital literacy, a psychological mandate for physical artifacts as transaction validation, and a preference for real-time interpersonal encounters. Adaptive institutional countermeasures specifically on-site digital mentorship and hybrid validation mechanisms have been strategically deployed to attenuate this sociocultural disconnect.